Portlandia. Season six [videorecording (DVD)] - Armisen, Fred, 1966-; Brownstein, Carrie, 1974- (Video Service Corp., 2016)
Each episode's character-based shorts draw viewers into 'Portlandia,' the dreamy and absurd rendering of Portland, Oregon. Season one inhabitants include: the owners of a feminist bookstore; a militant bike messenger; an artsy couple who attach cut-outs of birds to everything ('put a bird on it!'); an organic farmer who turns out to be a cult leader; and a couple negotiating a safe word to help govern their love life.